دراسة مقارنة بين مجاميع مختلفة باستخدام منحنيات الاستجابة - خلف، يوسف محمد (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2008)
من المواضيع الإحصائية الواسعة الاستخدام في التطبيق اعتمدت منحنيات الاستجابة كواحد من أهم المواضيع خصوصية في قطاعات الإنتاج الزراعي والحيواني وكذلك في القطاع الصحي. إن إمكانية تكييف الحالات المراد بحثها وتطبيقها في كلا نوعي الإحصاء المعلمي واللامعمي هو ما يعزز أهمية منحنيات الاستجابة. وغالبا ما تستخدم منحنيات الاستجابة للكشف عن الاختلافات في النمو والاستجابة بين مجموعتين أو أكثر على أساس اعتماد إحدى المجاميع باعتبارها مجموعة سيطرة على أن يتم تقدير منحني النمو لكل مفردة من المفردات بشكل مستقل. From a statistical subjects which have a wide using in application . Response curves had based as one of the more important subjects specially in agricultural and animal production sectors so as in healthy sector. The adjustment ability in states that is wanted to be searched and applied it in both kinds of parametric and nonparametric statistic is what supported the importance of response curves .Often response curves was using to discover the differences in growth and response between two groups or more based on one of the groups by considered it as a control group , to estimate the growth curve for one individual with independent form.
Keywords: الدراسات المقارنة -- منحنيات الاستجابة -- الأساليب الإحصائية -- التحليل الإحصائي -- الإحصاء